2013
DOI: 10.5243/jsswr.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Nonacademic Factors Associated with Dropping Out of High School: Adolescent Problem Behaviors

Abstract: This study uses a social capital and collective socialization lens to examine nonacademic factors in middle school that predict students' failure to complete high school, and focuses on youth who engage in adolescent problem behaviors of smoking cigarettes, sexual intercourse, delinquency, marijuana use, and alcohol use. Our area of interest was the extent to which these variables were predictive of dropping out of high school measured 6 years later and beyond the traditional variables of school performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
8
0
9
Order By: Relevance
“…Today, adolescents not enrolled in school are considered “dropouts” or “early school leavers” (Entwisle, Alexander, & Olson, 2004; Lamb & Markussen, 2011; UNESCO Institute for Statistics, 2012), but these categories often include students who have been “pushed” out of school because of academic failure or “antisocial” behavior (Bradley & Renzulli, 2011). Early leavers include students with physical disabilities, intellectual impairment, psychological disturbances, drug or alcohol addictions, convictions for criminal behavior, and those who are parents (Hawkins, Jaccard, & Needle, 2013; Hosley, 2003; Sliwka, 2008). To date, more than 100 different indicators of vulnerability have been defined (Bowers & Sprott, 2012; Bowers, Sprott, & Taff, 2013; Morrison & Shoon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Today, adolescents not enrolled in school are considered “dropouts” or “early school leavers” (Entwisle, Alexander, & Olson, 2004; Lamb & Markussen, 2011; UNESCO Institute for Statistics, 2012), but these categories often include students who have been “pushed” out of school because of academic failure or “antisocial” behavior (Bradley & Renzulli, 2011). Early leavers include students with physical disabilities, intellectual impairment, psychological disturbances, drug or alcohol addictions, convictions for criminal behavior, and those who are parents (Hawkins, Jaccard, & Needle, 2013; Hosley, 2003; Sliwka, 2008). To date, more than 100 different indicators of vulnerability have been defined (Bowers & Sprott, 2012; Bowers, Sprott, & Taff, 2013; Morrison & Shoon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study reported that 15-year-old students who performed poorly at school smoked six times more often during a week than high-grade achievers [ 23 ]. It is also shown that engaging in regular smoking during middle school could predict absence in high school classes independent of school performance during middle school [ 24 ]. Social factors could play a significant role in smoking initiation among youth.…”
Section: Introductionmentioning
confidence: 99%
“…El fracaso escolar se puede abordar desde dos perspectivas macro, las cuales se sustentan en variables de índole extraescolar e intraescolar, respectivamente. Desde el primer paradigma, las principales causales del abandono escolar se atribuyen a la situación socioeconómica (De Witte & Rogge, 2013;Ingrum, 2007;Rumberger & Lim, 2008;Rumberger & Thomas, 2000) y al contexto familiar Preal, 2003), aunque también se mencionan aspectos como la pobreza y la vulnerabilidad (Peña & Toledo, 2017), la búsqueda de trabajo, el origen étnico, la desintegración familiar y las limitadas expectativas de la familia con respecto a la educación (Castillo, 2003;Espinoza, Castillo, González, & Loyola, 2014a;Espinoza et al 2014b;Foley, Gallipoli, & Green, 2014;Hawkins, Jaccard, & Needle, 2013;Pomerantz, Moorman, & Litwack, 2007;).…”
Section: Marco Teóricounclassified